2002
DOI: 10.1016/s1044-0305(02)00414-2
|View full text |Cite
|
Sign up to set email alerts
|

Sequence dependent fragmentation of peptides generated by MALDI quadrupole time-of-flight (MALDI Q-TOF) mass spectrometry and its implications for protein identification

Abstract: A study has been undertaken to evaluate the usefulness of MALDI Q-TOF data for protein identification. The comparison of MS data of protein digests obtained on a conventional MALDI TOF instrument to the MS data from the MALDI Q-TOF reveal peptide patterns with similar intensity ratios. However, comparison of MS/MS Q-TOF data produced by nanoelectrospray versus MALDI reveals striking differences. Peptide fragment ions obtained from doubly charged precursors produced by nanoelectrospray are mainly y-type ions wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
75
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(77 citation statements)
references
References 18 publications
2
75
0
Order By: Relevance
“…An alternate approach described here takes advantage of the complementary nature of ESI and MALDI and utilizes a split-flow, parallel analysis scheme with data dependent MS/MS acquisitions. This combined technique facilitates the interrogation of both multiply (produced by ESI) and singly (produced by MALDI) charged precursor ions and provides complementary information for database searching [8,9]. Medzihradszky et al [21] and Juhasz et al [22] have reported similar findings in which more comprehensive characterization of complex protein digests were obtained by using ESI/MS/MS, MALDI/ MS, and/or MALDI/MS/MS analyses.…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…An alternate approach described here takes advantage of the complementary nature of ESI and MALDI and utilizes a split-flow, parallel analysis scheme with data dependent MS/MS acquisitions. This combined technique facilitates the interrogation of both multiply (produced by ESI) and singly (produced by MALDI) charged precursor ions and provides complementary information for database searching [8,9]. Medzihradszky et al [21] and Juhasz et al [22] have reported similar findings in which more comprehensive characterization of complex protein digests were obtained by using ESI/MS/MS, MALDI/ MS, and/or MALDI/MS/MS analyses.…”
mentioning
confidence: 93%
“…Matrix assisted laser desorption ionization (MALDI) in conjunction with MS/MS analysis has also been used to acquire product ion spectra from proteomic samples, generating data sets both analogous to and complementary with those produced by LC/ESI/MS/MS [8 -12]. While differences in the spectral content of MALDI/MS/MS and ESI/MS/MS of the same peptides have been described [9,10,13], there has been less discussion focused on findings that analysis of the same sample by both LC/ESI/MS/MS and LC/MALDI/MS/MS gives rise to improved proteome coverage at both the peptide and protein level.…”
mentioning
confidence: 99%
“…Statistical [19 -24] and mechanistic [25][26][27][28][29][30][31][32] analyses have led to a better understanding of peptide fragmentation behavior. Specifically, these studies have revealed residuespecific preferential cleavage N-terminal to proline (Pro), C-terminal to aspartic acid (Asp) and glutamic acid (Glu), and C-terminal to oxidized cysteine (e.g., cysteine sulfinic acid and cysteine sulfonic acid) [19,20,[33][34][35][36][37][38][39][40][41][42][43]. The dominance of these preferential cleavages may lead to a loss of fragmentation information because other fragment peaks may be of very low intensity or not present.…”
mentioning
confidence: 99%
“…The completeness of the observed fragmentation series depends on the particular sequence of the peptide under study, the charge state of the ion produced, and the mode by which the fragmentation is induced within the mass spectrometer. By and large, doubly charged peptide ions tend to fragment more evenly across a given sequence than do singly charged ion species ( [40,44,51] and extensive personal observations). Thus, a large proportion of de novo sequencing has been performed on doubly charged ions, which are readily produced from tryptic peptides by electrospray ionization (ESI).…”
mentioning
confidence: 99%
“…By contrast, MALDI produces predominantly singly charged ions from peptides. These singly charged ion species often yield relatively low complexity CID mass spectra that tend to be dominated by a few preferred fragmentation pathways [40,[52][53][54][55][56]. When this fragmentation is induced on the slow time scale of resonant excitation within an ion trap mass spectrometer, the dissociation of singly-charged ions becomes especially selective, occurring largely adjacent to any aspartyl, glutamyl, or prolyl residues that may be present in the peptide [54,56].…”
mentioning
confidence: 99%